2016
DOI: 10.1002/pi.5195
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanofibrous assemblies based on β‐sheet‐forming peptides for biomedical applications

Abstract: Amyloid fibrils are supramolecular polymers with -sheet-rich structures formed by polymerization of protein/peptide with intermolecular interaction. Amyloid fibrils have been miscast as toxic villains since they have historically been studied as pathogens associated with serious diseases, including Alzheimer's and Parkinson's disease. However, recent studies on their toxicity and formation mechanism and discovery of their functionality in nature correct the misconception and strongly facilitate the possible us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Finally, the KCK-CPT prodrug was converted to the active form by glutathione (GSH) in the cytoplasm, inducing apoptosis in the cancer cell. Waku and Tanaka showed that self-assembling peptide nanofibrils can be used as potential delivery agents for vaccines 410,411. Highly antigen-loaded nano-assemblies were formed by conjugating antigens to β-sheet-forming peptides.…”
Section: Various Applications Of Amyloid-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…Finally, the KCK-CPT prodrug was converted to the active form by glutathione (GSH) in the cytoplasm, inducing apoptosis in the cancer cell. Waku and Tanaka showed that self-assembling peptide nanofibrils can be used as potential delivery agents for vaccines 410,411. Highly antigen-loaded nano-assemblies were formed by conjugating antigens to β-sheet-forming peptides.…”
Section: Various Applications Of Amyloid-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…β -Sheet peptides have a high propensity to self-assemble in aqueous solutions and have thus been the focus of intense study as supramolecular materials. 27,116118 Amyloid aggregates are an example of β -sheet assemblies that have been of special interest due to their relevance to protein folding disorders. 2,119,120 These materials have inspired the development of engineered β -sheet aggregates, which tend to be one-dimensional fibrils or nanoribbons that lack functional cytotoxicity and exhibit useful emergent properties that notably include the formation of entangled hydrogel networks.…”
Section: β-Sheet Peptidesmentioning
confidence: 99%
“…The development of biomaterials derived from self‐assembled peptides is of great current interest due to biomedical applications including controlled release drug delivery, vaccine development, tissue engineering, and wound healing . Amphipathic peptides that consist of alternating hydrophobic and hydrophilic amino acids are a privileged class of peptide that readily self‐assembles into β‐sheet bilayer nanoribbons that share the basic characteristics of cross‐β amyloid assemblies (Figure ) .…”
Section: Introductionmentioning
confidence: 99%